Use of algae as food ingredient: sensory acceptance and commercial products - Matos, Ângelo Paggi; Novelli, Enrico; Tribuzi, Giustino (Frontiers in Food Science and Technology, 2022)
Algal biomass or algae extracts can be used as food ingredients, meeting the needs of the consumers for nutritious, sustainable, and healthy food. Microalgae and macroalgae (seaweed) are rich in proteins, soluble fibers and polysaccharides, lipids and polyunsaturated fatty acids, pigments, vitamins, and minerals. However, one of the main challenges of using algae in food systems is related to the palatability of algae in terms of sensory as biomass may contain several odor-active volatile chemical compounds, which can be undesirable for certain algal-food product. This mini-review aim to provide an overview of nutritional compounds extracted from algae, while briefly discussing the main flavor compounds that directly affect the sensorial properties of algal biomass. Examples of new and sophisticated foods enriched with algal biomass such as plant-based fish, meat, and dairy analogues and innovative ingredients are also presented, elevating algae’s credibility as a potential source for novel food development.